Guidelines for blood pressure measurement: development over 30 years - Stergiou, GS; Parati, G; McManus, RJ; Head, GA; Myers, MG; Whelton, PK (Wiley, 2018)
In the last 2 decades, several scientific societies have published specific guidelines for blood pressure (BP) measurement, providing detailed recommendations for office, home, and ambulatory BP monitoring. These documents typically provided strong support for using out‐of‐office BP monitoring (ambulatory and home). More recently, several organizations recommended out‐of‐office BP evaluation as a primary method for diagnosing hypertension and for treatment titration, with office BP regarded as a screening method. Efforts should now be directed towards making ambulatory and home BP monitoring readily available in primary care and ensuring that such measurements are obtained by following current guidelines. Moreover, it should be mandatory for all published clinical research papers on hypertension to provide details on the methodology of the BP measurement.